2009
DOI: 10.1136/thx.2008.107946
|View full text |Cite
|
Sign up to set email alerts
|

Gelsolin expression is necessary for the development of modelled pulmonary inflammation and fibrosis

Abstract: Background: Despite intense research efforts, the aetiology and pathogenesis of idiopathic pulmonary fibrosis remain poorly understood. Gelsolin, an actinbinding protein that modulates cytoskeletal dynamics, was recently highlighted as a likely disease modifier through comparative expression profiling and target prioritisation. Methods: To decipher the possible role of gelsolin in pulmonary inflammation and fibrosis, immunocytochemistry on tissue microarrays of human patient samples was performed followed by c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 34 publications
6
46
0
Order By: Relevance
“…It is a key regulator of actin filament assembly and disassembly and is involved in maintaining cell structure and motility (49). Increased GSN expression is associated with interstitial fibrosis and inflammation (51), likely because of the GSN-mediated destabilization of cytoskeleton and increased movement of platelets and immune infiltrate, and GSN Ϫ/Ϫ mice are shown to develop decreased pulmonary fibrosis and inflammation (51). In the heart, GSN is shown to catalyze the disassembly and degradation of myocardial proteins (52), and its increased expression is detected in failing human hearts (52).…”
Section: Idmentioning
confidence: 99%
“…It is a key regulator of actin filament assembly and disassembly and is involved in maintaining cell structure and motility (49). Increased GSN expression is associated with interstitial fibrosis and inflammation (51), likely because of the GSN-mediated destabilization of cytoskeleton and increased movement of platelets and immune infiltrate, and GSN Ϫ/Ϫ mice are shown to develop decreased pulmonary fibrosis and inflammation (51). In the heart, GSN is shown to catalyze the disassembly and degradation of myocardial proteins (52), and its increased expression is detected in failing human hearts (52).…”
Section: Idmentioning
confidence: 99%
“…Our results are consistent with those from previous studies that showed that exposure to ZnO NPs mainly induces lung in ammation and immune response in rats. 3,22) Although S100A8 and S100A9, candidate markers of idiopathic pulmonary brosis and lung cancer, 23,24) were not identi ed, pulmonary surfactant-associated protein D and gelsolin, biomarkers of idiopathic pulmonary brosis, [35][36][37] were signi cantly up-regulated in rat BALF a er ZnO NPs exposure (2.42-and 2.84-fold, respectively). Although it is necessary to further clarify the potential health risks associated with exposure to zinc oxide nanoparticles, the results obtained by gel-based proteomic analysis in this study and those obtained by an LC-based proteomic approach in our previous study 22) indicate that these in ammatory responses might induce idiopathic pulmonary brosis or lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the concentration of gelsolin in patients with idiopathic pulmonary brosis or brotic non-speci c interstitial pneumonia is higher than in healthy individuals. 36,37) Although LC-based approach shown many advantages, one of the most important bene t of the gel-based method is that this technology can detect di erent molecular forms. For example, Mitsumoto et al reported that protein deglycase DJ-1 appeared as two di erent major molecular forms on 2DE gel, pI 5.8 (DJ-1/5.8) and pI 6.2 (DJ-1/6.2).…”
Section: Resultsmentioning
confidence: 99%
“…Caspase-3-mediated gelsolin fragmentation has been proposed to be an apoptotic effector mechanism in COPD pathogenesis and a marker of lung injury. 32 Alterations in gelsolin expression have been associated with cigarette smoking and different pulmonary diseases such as fibrosis; however, little is known about the role of gelsolin in COPD. [32][33][34] Gelsolin activates PI3K/Akt pathway, 35 which regulates cell growth, proliferation, adhesion, migration and survival.…”
Section: Discussionmentioning
confidence: 99%
“…32 Alterations in gelsolin expression have been associated with cigarette smoking and different pulmonary diseases such as fibrosis; however, little is known about the role of gelsolin in COPD. [32][33][34] Gelsolin activates PI3K/Akt pathway, 35 which regulates cell growth, proliferation, adhesion, migration and survival. Interestingly, it promotes the differentiation of alveolar epithelial type I and II cells from alveolar epithelial stem cells.…”
Section: Discussionmentioning
confidence: 99%